Inductive decision tree analysis of the validity rank of construction parameters of innovative gear pump after tooth root undercutting - Deptuła, Adam; Partyka, Marian (Zielona Góra: Uniwersytet Zielonogórski)
The article presents an innovative use of inductive algorithm for generating the decision tree for an analysis of the rank validity parameters of construction and maintenance of the gear pump with undercut tooth. It is preventer an alternative way of generating sets of decisions and determining the hierarchy of decision variables to existing the methods of discrete optimization.
Keywords: inductive decision tree; gear pump; tooth root undercutting; validity rank of the construction parameter; optimization